ORGANIZATION OF PEDAGOGICAL EXPERIMENTAL WORK AND ANALYSIS OF ITS RESULTS WHEN TEACHING GENERAL AND MEDICAL RADIOBIOLOGY AT UNIVERSITIES. (World Bulletin of Public Health, 2023)
In this article, the application of the results of pedagogical research in the educational process is important and shows the effectiveness of research work; high rates have been achieved in the formation of relevant knowledge. The experimental work was carried out during 2020-2023, the experimental and control groups were selected from among students of the Tashkent Medical Academy, Samarkand State Medical University and Bukhara State Medical University.
Keywords: General and medical radiobiology; Pearson Chi-square